The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1445-5994.2003.00360.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different aspirin doses on platelet aggregation in patients with stable coronary artery disease

Abstract: Our results demonstrate that doses of aspirin less than 100 mg are not as effective at inhibiting platelet aggregation as doses greater than 100 mg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Recently though, a randomized study of 60 patients with stable coronary artery disease showed that the effect of aspirin was dose-dependent and the conclusion was that doses of less than 100 mg of aspirin was less effective inhibiting platelet aggregation than doses greater than 100 mg [22]. This could indicate that higher doses of aspirin could be necessary to inhibit increased activity in the thromboxane positive feedback system, but for the time being there is no clear evidence saying that higher doses of aspirin improve clinical outcome [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently though, a randomized study of 60 patients with stable coronary artery disease showed that the effect of aspirin was dose-dependent and the conclusion was that doses of less than 100 mg of aspirin was less effective inhibiting platelet aggregation than doses greater than 100 mg [22]. This could indicate that higher doses of aspirin could be necessary to inhibit increased activity in the thromboxane positive feedback system, but for the time being there is no clear evidence saying that higher doses of aspirin improve clinical outcome [1].…”
Section: Discussionmentioning
confidence: 99%
“…ADP is released by activated platelets, but also in the heart from cardiac myocytes during ischemia, or from endothelial cells, red blood cells and sympathetic nerves [22,23]. Erythrocytes are known to contain large amounts of ADP, which may increase the platelet activity and modulate the effect of aspirin [24].…”
Section: Discussionmentioning
confidence: 99%
“…17 However, a number of studies provide evidence for VPR with aspirin, including a markedly reduced response to platelet function tests in some patients. Decreased aspirin responsiveness occurred in 8.3% of healthy volunteers, 18 7.2% to 36% of CVD patients, 19 -22 60% of PAD patients, 23 and 5.5% to 43% of CAD patients 16,24 -28 (Table 1).…”
Section: Aspirinmentioning
confidence: 98%
“…As little as 81mg of aspirin will impede aggregation by this test. 51 Multiple Electrode Aggregometry (MEA) is a newly developed technique for testing platelet function in whole blood based on classic whole-blood impedance aggregometry. MEA does not require a specialized coagulation laboratory and may be useful for point-of-care analysis.…”
Section: Importance Of Laboratory Testsmentioning
confidence: 99%